Determination of acetamiprid, imidacloprid, and spirotetramat and their relevant metabolites in pistachio using modified QuEChERS combined with liquid chromatography-tandem mass spectrometry. (1st February 2018) - Faraji, Mohammad; Noorbakhsh, Roya; Shafieyan, Hooshang; Ramezani, Mohammadkazem
Highlights: QuEChERS extraction procedure for pesticides determination in pistachio samples. Acetamiprid, imidacloprid, and spirotetramat and their relevant metabolites were determined. Efficient extraction and clean-up with negligible matrix effect were obtained. Satisfactory linearity, recoveries, accuracy and precision were obtained. Abstract: A QuEChERS based methodology was developed for the simultaneous identification and quantification of acetamiprid, imidacloprid, and spirotetramat and their relevant metabolites in pistachio by liquid chromatography-tandem mass spectrometry for the first time. First, sample extraction was done with MeCN:citrate buffer:NaHCO3 followed by phase separation with the addition of MgSO4 :NaCl. The supernatant was then cleaned by a primary-secondary amine (PSA), GCB, and MgSO4 . The proposed method provides a linearity in the range of 5–200 µg L −1, and the linear regression coefficients were higher than 0.99. LOD and LOQ were obtained to be 2 and 5 µg kg −1 for the studied insecticides, respectively, with the exception of imidacloprid-olefin (5 and 10 µg kg −1 ). Acceptable recoveries (91–110%) were obtained for all the analytes with good intra- and inter-precisions (0.4 ≥ RSD ≤11.0). The method was then used for the pistachio samples collected from a field trial to estimate the maximum residue limits (MRLs) in next step.